If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 = 3(2x + -3) Reorder the terms: 27 = 3(-3 + 2x) 27 = (-3 * 3 + 2x * 3) 27 = (-9 + 6x) Solving 27 = -9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 27 + -6x = -9 + 6x + -6x Combine like terms: 6x + -6x = 0 27 + -6x = -9 + 0 27 + -6x = -9 Add '-27' to each side of the equation. 27 + -27 + -6x = -9 + -27 Combine like terms: 27 + -27 = 0 0 + -6x = -9 + -27 -6x = -9 + -27 Combine like terms: -9 + -27 = -36 -6x = -36 Divide each side by '-6'. x = 6 Simplifying x = 6
| 4-5x+20-6x=68 | | 8x+28=4(x+5) | | -36=8x-11x | | 8(x-10)=-92 | | (x-8)+x+(x+x-8)*0.75=70 | | (x^2+x)-(x+2)=0 | | (1,06²²-1)/(1,06²²,065) | | 7/2x=105 | | 2x+3(4+4)=2x+3(4) | | 422/x=9 | | -10x=10-10 | | Tan-1(8/3)=69.4 | | 2(4x-5)=-38 | | x^2+y^2+4x+5=0 | | 10+(x-1)10=200 | | log^3x=17 | | 6(3n-1)=4(n+4) | | 8+5y=8900 | | 15x-1=9-5x | | 3q=11q | | 18x^2+25x-15=0 | | 4(2x-6)=3c | | 73*10+6+-13=723 | | 73*10+6-13=723 | | 4c+4d+2c-8d= | | z+2iz=2i+1 | | 9x-100=3x-10 | | -3-4x=5-6x | | 36/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4=0 | | 3x+9=31-5x | | 36/0.4=1231 | | 36/0.4=0 |